Microbe-based therapies for colorectal cancer: Advantages and limitations. (November 2022) - Saeed, Mohd; Shoaib, Ambreen; Kandimalla, Raghuram; Javed, Shamama; Almatroudi, Ahmad; Gupta, Ramesh; Aqil, Farrukh
Abstract: Cancer is one of the leading global causes of death in both men and women. Colorectal cancer (CRC) alone accounts for ∼10 % of total new global cases and poses an over 4% lifetime risk of developing cancer. Recent advancements in the field of biotechnology and microbiology concocted novel microbe-based therapies to treat various cancers, including CRC. Microbes have been explored for human use since centuries, especially for the treatment of various ailments. The utility of microbes in cancer therapeutics is widely explored, and various bacteria, fungi, and viruses are currently in use for the development of cancer therapeutics. The human gut hosts about 100 trillion microbes that release their metabolites in active, inactive, or dead conditions. Microbial secondary metabolites, proteins, immunotoxins, and enzymes are used to target cancer cells to induce cell cycle arrest, apoptosis, and death. Various approaches, such as dietary interventions, the use of prebiotics and probiotics, and fecal microbiota transplantation have been used to modulate the gut microbiota in order to prevent or treat CRC pathogenesis. The present review highlights the role of the gut microbiota in CRC precipitation, the potential mechanisms and use of microorganisms as CRC biomarkers, and strategies to modulate microbiota for the prevention and treatment of CRC.